Diversity of TCR repertoire predicts recurrence after CRT followed by durvalumab in patients with NSCLC - Masayuki Shirasawa; Tatsuya Yoshida; Takaji Matsutani; Yuki Takeyasu; Naoko Goto; Shigehiro Yagishita; Shigehisa Kitano; Hiroaki Kuroda; Toyoaki Hida; Takayasu Kurata; Yuichiro Ohe (npj Precision Oncology)
Abstract Chemoradiotherapy (CRT) followed by durvalumab is standard for unresectable locally advanced non-small-cell lung cancer (LA-NSCLC). This study assesses how CRT alters the T-cell receptor (TCR) repertoire in CD8 + PD-1 + T-cells and its impact on clinical outcomes. This prospective study, conducted from November 2019 to May 2021 at three institutions in Japan, evaluated the diversity of TCR repertoire (DE50) in PD-1 + CD8 + T-cells and CD8 + T-cell phenotypes in peripheral blood before and after CRT. Forty patients treated with CRT were included. The diversity and usage of TCR beta variable chains (TRBV) and 14 junctional chains (TRBJ) were significantly and positively correlated before and after CRT. Regarding the DE50, the progression-free survival (PFS) of patients with DE50High before CRT was significantly greater than that of those with DE50Low (NR vs. NR months, HR 0.17, p = 0.01). The diversity of TCR repertoire might more accurately predict the efficacy of CRT followed by durvalumab therapy.